Waste vinegar residue additive for polypropylene grafted tobacco, preparation method and application thereof

By grafting the waste vinegar residue for tobacco and polypropylene grafted maleic anhydride, an auxiliary agent is prepared and applied to PP/modified bamboo powder composite materials, the problem of poor compatibility between PP and bamboo powder is solved, the mechanical and thermodynamic properties of the material are improved, and the waste reuse is realized.

CN119285965BActive Publication Date: 2025-05-09HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411306793.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-05-09
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Poor compatibility between polypropylene (PP) and bamboo powder (BF), resulting in insufficient mechanical and thermodynamic properties, and environmental pollution problems exist in the recycling and treatment of waste vinegar residue for smoke.

Method used

By grafting the waste vinegar residue for tobacco and polypropylene grafted maleic anhydride in an organic solvent, a waste vinegar residue additive for polypropylene grafted tobacco was prepared and applied to the melt extrusion of PP/modified bamboo powder.

Benefits of technology

The mechanical properties and thermodynamic properties of PP/modified bamboo powder composite materials have been improved, the recycling of waste has been realized, the high-value utilization of biomass resources has been promoted, and the problems such as "white pollution" have been solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285965B_ABST
    Figure CN119285965B_ABST
Patent Text Reader

Abstract

The invention discloses a polypropylene grafted tobacco waste vinegar residue auxiliary agent, a preparation method and an application thereof. First, the tobacco waste vinegar residue is dissolved in tetrahydrofuran; then, polypropylene grafted maleic anhydride dissolved in xylene is added to the above solution for grafting reaction, and then precipitation, washing and drying are performed to obtain a plasticizing and compatibility integrated auxiliary agent polypropylene grafted tobacco waste vinegar residue; then, bamboo powder is added to tetrahydrofuran, triethylamine and phthaloyl chloride are added to the above suspension for reaction, and then precipitation, washing and drying are performed to obtain hydrophobically modified bamboo powder; finally, the auxiliary agent is applied to the melt extrusion of polypropylene / modified bamboo powder to obtain a master batch. The invention uses the tobacco waste vinegar residue to prepare the plasticizing and compatibility integrated auxiliary agent, realizes the technical innovation of waste recycling, and applies the auxiliary agent to the melt extrusion of polypropylene / modified bamboo powder to obtain a master batch with improved mechanical properties and thermodynamic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polypropylene modification, in particular to a polypropylene grafted tobacco waste vinegar residue additive, a preparation method and application thereof. Background Art

[0002] Polypropylene (PP) has the advantages of high thermal stability, good melt fluidity, high tensile strength, impact strength and elastic modulus, strong electrical insulation and chemical corrosion resistance. Its products have good gloss and are odorless and non-toxic, so they are widely used in various fields such as automobiles, textiles, packaging and electronics. However, there are still many shortcomings, such as high low-temperature brittleness, poor high-temperature weathering resistance, and large molding shrinkage, which greatly limit the production and application of PP. Filling and modifying PP can effectively improve the mechanical properties of PP. Composite materials prepared by reinforcing PP with bamboo powder (BF) have the advantages of low density, low price, easy degradation, good processing performance and low equipment loss. However, since the surface of BF is covered with a large number of hydroxyl functional groups, the surface energy is high, the polarity is strong, and the compatibility with the non-polar polymer matrix is ​​poor, it cannot play a good reinforcing role.

[0003] my country is a major consumer and producer of cigarettes. The base material of cigarette filters is cellulose diacetate (a thermoplastic resin, which is essentially different from biomass cellulose). In the production process of cigarette filters, at least 10% of by-product vinegar residue is generated. The main components of waste vinegar residue from tobacco are still cellulose diacetate sheets, as well as a small amount of cellulose triacetate, lignin, titanium dioxide and other components. Waste vinegar residue from tobacco is usually disposed of by landfill, which not only requires processing costs but also pollutes the environment. Effective recycling of it can not only save resources but also create economic value.

[0004] In order to improve the compatibility of PP and BF, the common method is to hydrophobically modify BF or to increase the capacity of the PP / BF system by adding a compatibilizer. For example, firstly treat BF with alkali, then add the alkali-treated BF to an ethanol solution containing a silane coupling agent for reaction, and finally dry it to obtain silane-modified BF. This method can effectively improve the roughness of the surface and interior of BF and enhance the density and uniformity of the composite material; however, the process of modification after alkali treatment is cumbersome and complicated, which is not conducive to the continuity of the production process. For another example, the compatibilization effect of maleic anhydride grafted polypropylene compatibilizer can solve the problems of poor compatibility and easy agglomeration between PP and BF; however, this type of compatibilizer still has the disadvantages of low grafting efficiency and high monomer residue, which leads to poor compatibility between PP and BF and reduced mechanical properties. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a polypropylene grafted tobacco waste vinegar residue additive, a preparation method and an application thereof, thereby realizing the recycling of waste. The additive is applied to the melt extrusion of polypropylene / modified bamboo powder to obtain a masterbatch with improved mechanical properties and thermodynamic properties.

[0006] The invention provides a method for preparing a polypropylene grafted tobacco waste vinegar residue auxiliary agent, which comprises the following steps: subjecting tobacco waste vinegar residue and polypropylene grafted maleic anhydride to a grafting reaction in an organic solvent, and obtaining the polypropylene grafted tobacco waste vinegar residue auxiliary agent after precipitation, washing and drying.

[0007] Preferably, the mass ratio of polypropylene grafted maleic anhydride to tobacco waste vinegar residue is 1:0.2-0.5.

[0008] Preferably, the grafting reaction temperature is 115-135° C., and the reaction time is 3-5 h.

[0009] The invention provides a waste vinegar residue auxiliary agent for polypropylene grafted tobacco prepared by the method.

[0010] The present invention provides an application of the polypropylene grafted tobacco waste vinegar residue additive in a PP / modified bamboo powder composite material.

[0011] Preferably, the method comprises the following steps: mixing polypropylene, modified bamboo powder and polypropylene grafted tobacco waste vinegar residue auxiliary agent at high speed and then melt-extruding.

[0012] Preferably, the mass ratio of polypropylene, modified bamboo powder and polypropylene grafted tobacco waste vinegar residue additive is 5:1:0.025-0.075.

[0013] Preferably, the conditions for melt extrusion are: screw speed of 200-300 rpm, feeding rate of 5-7 Hz, and extrusion temperature zones are set to 165, 170, 170, 175, 180, 185, 190, 190, 190, 185, 180°C.

[0014] Preferably, the method for preparing the modified bamboo powder comprises the following steps: adding bamboo powder to tetrahydrofuran, then adding triethylamine and phthaloyl chloride to react, and obtaining the modified bamboo powder after precipitation, washing and drying.

[0015] Preferably, the mass ratio of bamboo powder, triethylamine and phthaloyl chloride is 1:0.05-0.1:0.05-0.1; the reaction temperature is 40-50° C., and the reaction time is 4-6 hours.

[0016] Beneficial technical effects of the present invention:

[0017] (1) In the present invention, polypropylene grafted maleic anhydride and tobacco waste vinegar residue undergo esterification reaction to obtain polypropylene grafted tobacco waste vinegar residue, and the structure of tobacco waste vinegar residue is changed by esterification reaction, thereby plasticizing tobacco waste vinegar residue, improving its thermodynamic properties, and also playing the role of a compatibilizer. At the same time, the recycled tobacco waste vinegar residue realizes the technical innovation of waste recycling, promotes the process of high-value utilization of biomass resources, and opens up a new way to solve problems such as "white pollution".

[0018] (2) In the present invention, the surface of bamboo powder contains a large number of hydroxyl groups, which can effectively reduce the surface wettability and surface reactivity of bamboo powder through nucleophilic addition reaction with phthaloyl chloride, increase the crystallization rate of cellulose molecules, further improve the mechanical meshing of bamboo powder and polypropylene resin matrix, enhance the density and uniformity of the composite material, and improve the mechanical strength of the material.

[0019] (3) In the present invention, the tobacco waste vinegar residue is grafted onto polypropylene through an esterification reaction, and the bamboo powder is surface-modified using phthaloyl chloride by a nucleophilic addition reaction. During melt extrusion granulation, the polypropylene grafted tobacco waste vinegar residue, the modified bamboo powder and the polypropylene are bonded and cross-linked to form a network structure under the action of chemical bonds and hydrogen bonds, thereby improving the mechanical properties of the polypropylene composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 FTIR comparison chart of PP-g-MAH, CWVR and additive PP-g-CWVR proposed in the present invention;

[0021] Figure 2 FTIR comparison diagram of BF and P-BF proposed in the present invention;

[0022] Figure 3 The crystallization / melting curve comparison diagram of PP, PP / P-BF, and PP / P-BF / additive PP-g-CWVR proposed in the present invention; (a) is the crystallization process of temperature drop, and (b) is the melting process of temperature rise;

[0023] Figure 4 This is a schematic diagram of the synthesis mechanism of the additive PP-g-CWVR proposed in the present invention;

[0024] Figure 5 Schematic diagram of the BF modification mechanism proposed in the present invention;

[0025] Figure 6 Schematic diagram of the action mechanism of the additive PP-g-CWVR proposed in the present invention in the PP / P-BF system. DETAILED DESCRIPTION

[0026] The present invention will be further explained below in conjunction with specific embodiments.

[0027] The polypropylene (PP), polypropylene grafted maleic anhydride (PP-g-MAH), tobacco waste vinegar residue (CWVR), bamboo powder (BF), triethylamine (TEA), phthaloyl chloride (PD), tetrahydrofuran, xylene, etc. in the embodiments of the present invention are all commercially available.

[0028] Example 1

[0029] The method steps for preparing the PP / modified bamboo powder composite material proposed in this scheme are as follows:

[0030] S1: First, weigh 4 g of CWVR and dissolve it in 100 mL of tetrahydrofuran at room temperature, then weigh 20 g of PP-g-MAH and add it to 100 mL of xylene, and heat it to 115°C until it is completely dissolved; then, add the CWVR solution to the PP-g-MAH solution, react at 115°C for 4 hours, and obtain a grafted solution.

[0031] S2: Pour the above solution into a beaker containing 110 mL of methanol and stir continuously with a glass rod to precipitate the product; then, filter the suspension to obtain a pre-product; place the pre-product in an oven at 80°C and dry for 4 hours to obtain the additive PP-g-CWVR.

[0032] S3: Weigh 300 g of BF and add it to 500 mL of tetrahydrofuran to form a suspension; then, raise the temperature to 50° C., drop 19.2 mL of TEA into the suspension; then, add 10.6 mL of PD and react for 5 hours to obtain a product solution.

[0033] S4: Pour the above solution into a beaker containing 110 mL of methanol and stir with a glass rod to precipitate the product; then, filter the suspension to obtain a pre-product. Dry the pre-product in an oven at 80°C for 4 hours to obtain modified bamboo powder (P-BF).

[0034] S5: 1 kg PP, 0.2 kg P-BF and 10 g additive PP-g-CWVR were weighed and mixed at high speed to obtain a mixture.

[0035] S6: melt-extrude the mixture described in S5, the screw speed is 200 rpm, the feeding rate is 5 Hz, and the extrusion temperature zones are set to 160, 165, 170, 175, 180, 185, 190, 190, 190, 185, and 180°C.

[0036] Example 2

[0037] The method steps for preparing the PP / modified bamboo powder composite material proposed in this scheme are as follows:

[0038] S1: First, weigh 4 g of CWVR and dissolve it in 100 mL of tetrahydrofuran at room temperature, then weigh 20 g of PP-g-MAH and add it to 100 mL of xylene, and heat it to 135°C until it is completely dissolved; then, add the CWVR solution to the PP-g-MAH solution, react at 135°C for 4 hours, and obtain a grafted product solution.

[0039] S2: Pour the above solution into a beaker containing 110 mL of methanol and stir continuously with a glass rod to precipitate the product; then, filter the suspension to obtain a pre-product; place the pre-product in an oven at 80°C and dry for 4 hours to obtain the additive PP-g-CWVR.

[0040] S3: Weigh 300g of BF and add it to 500mL of tetrahydrofuran to form a suspension; then, raise the temperature to 50°C, and drop 19.2mL of TEA into the suspension; then, add 10.6mL of PD and react for 5h to obtain a product solution.

[0041] S4: Pour the above solution into a beaker containing 110 mL of methanol and stir continuously with a glass rod to precipitate the product; then, filter the suspension to obtain a pre-product. Dry the pre-product in an oven at 80°C for 4 hours to obtain P-BF.

[0042] S5: 1 kg PP, 0.2 kg P-BF and 10 g additive PP-g-CWVR were weighed and mixed at high speed to obtain a mixture.

[0043] S6: melt-extrude the mixture described in S5, the screw speed is 200 rpm, the feeding rate is 5 Hz, and the extrusion temperature zones are set to 160, 165, 170, 175, 180, 185, 190, 190, 190, 185, and 180°C.

[0044] Example 3

[0045] The method steps for preparing the PP / modified bamboo powder composite material proposed in this scheme are as follows:

[0046] S1: First, weigh 4 g of CWVR and dissolve it in 100 mL of tetrahydrofuran at room temperature, then weigh 20 g of PP-g-MAH and add it to 100 mL of xylene, and heat it to 115°C until it is completely dissolved; then, add the CWVR solution to the PP-g-MAH solution, react at 115°C for 4 hours, and obtain a grafted product solution.

[0047] S2: Pour the above solution into a beaker containing 110 mL of methanol and stir continuously with a glass rod to precipitate the product; then, filter the suspension to obtain a pre-product. Dry the pre-product in an oven at 80°C for 4 hours to obtain the additive PP-g-CWVR.

[0048] S3: Weigh 300g of BF and add it to 500mL of tetrahydrofuran to form a suspension; then, raise the temperature to 50°C, and drop 24.7mL of TEA into the above suspension; then, add 12.8mL of PD and react for 5h to obtain a product solution.

[0049] S4: Pour the above solution into a beaker containing 110 mL of methanol and stir continuously with a glass rod to precipitate the product; then, filter the suspension to obtain a pre-product. Dry the pre-product in an oven at 80°C for 4 hours to obtain P-BF.

[0050] S5: 1 kg PP, 0.2 kg P-BF and 10 g additive PP-g-CWVR were weighed and mixed at high speed to obtain a mixture.

[0051] S6: melt-extrude the mixture described in S5, the screw speed is 200 rpm, the feeding rate is 5 Hz, and the extrusion temperature zones are set to 160, 165, 170, 175, 180, 185, 190, 190, 190, 185, and 180°C.

[0052] Comparative Example 1

[0053] The method steps for preparing the PP / modified bamboo powder composite material proposed in this scheme are as follows:

[0054] S1: 1 kg PP and 0.2 kg P-BF were weighed and mixed at high speed to obtain a mixture.

[0055] S2: The mixed material described in S1 was melt-extruded, the screw speed was 200 rpm, the feeding rate was 5 Hz, and the extrusion temperature zones were set to 160, 165, 170, 175, 180, 185, 190, 190, 190, 185, and 180°C.

[0056] The present invention conducts infrared tests on PP-g-MAH, CWVR and the integrated plasticizing and compatibilizing additive PP-g-CWVR. The results are as follows: Figure 1 As shown in the figure, the infrared absorption peak of PP-g-MAH is at 1780cm -1 There is an obvious absorption peak near it, which is the C=O stretching vibration absorption peak of MAH; the infrared absorption curve of CWVR is at 1748cm -1 The characteristic absorption peak of C=O vibration in the ester group appears at 1780cm -1 The characteristic peak of MAH at 1748 cm-1 completely disappeared, indicating that the anhydride group at the end of PP-g-MAH reacted with the hydroxyl group on CWVR. -1The intensity of the C=O vibration absorption peak increases, further indicating that the anhydride group and the hydroxyl group undergo a chemical reaction to form an ester, and the two are connected by chemical bonds to form a graft copolymer.

[0057] The present invention performs infrared testing on BF and P-BF, and the results are as follows: Figure 2 As shown in the figure, the modified BF is at 3348cm -1 The absorbance of the characteristic peak (stretching vibration of —OH) at 1734 cm-1 was different. The PD molecules can combine with the hydroxyl groups on the surface of BF, reducing the number of free hydroxyl groups, which is manifested as a decrease in the number of hydroxyl groups in the infrared spectrum. -1 The characteristic peak at is C=O stretching vibration, and the number of carbonyl groups increases in the infrared spectrum, which confirms that the hydroxyl groups on the BF surface undergo esterification reaction with the acyl chloride groups of PD, and PD is successfully coated on the BF surface in the form of chemical bonding.

[0058] The present invention tests the contact angle of BF and P-BF, and Table 1 shows the water contact angle of BF / P-BF. It can be seen that the contact angle of BF before modification is 76.4°, and the contact angle of BF after modification increases to 92.8°. BF has the function of a hydrophilic high surface energy substrate. Due to the chemical reaction between PD and BF, the polarity of BF fiber is weakened, the wettability is reduced, the hydrophobicity is enhanced, and the compatibility with PP plastic is enhanced.

[0059] Table 1 Water contact angle of BF / P-BF

[0060]

[0061] The present invention performs differential scanning calorimetry test on the PP sample, the sample of comparative example 1 and the sample of embodiment 1. The results are as follows: Figure 3 As shown in Figure 2, (a) is the crystallization process of cooling down, and (b) is the melting process of heating up. The details of the thermodynamic parameters of the samples are shown in Table 2.

[0062] Table 2 Thermodynamic parameters of samples

[0063]

[0064] Depend on Figure 3As can be seen from Table 2, compared with the PP sample, the melting temperature of the PP / P-BF sample in Comparative Example 1 dropped to 161.23°C, and the crystallization enthalpy and crystallinity dropped to 61.30 J / g and 25.39%, respectively. This shows that the addition of P-BF affects the crystallization properties of the material. P-BF hinders the free movement of the molecular chain segments of the plastic matrix, affecting its crystallization nucleation and grain growth; in addition, there are still hydroxyl groups on the surface of P-BF, which makes it have a certain polarity, and it is easy to agglomerate, which weakens the interface interaction between the fiber and the matrix, making it difficult to form heterogeneous nucleation, and the crystallinity is reduced accordingly. Compared with the PP / P-BF sample in Comparative Example 1, the melting temperature of the PP / P-BF / PP-g-CWVR sample in Example 1 shows a downward trend from 161.23°C to 158.45°C, indicating that the additive PP-g-CWVR can effectively improve the thermal properties of the PP / P-BF composite material; the crystallization enthalpy increases from 61.30 J / g to 72.19 J / g, and the crystallinity increases from 25.39% to 31.74%, indicating that PP-g-CWVR has a heterogeneous nucleation effect on PP / P-BF and can improve the crystallinity of the composite material.

[0065] Figure 4 This is a schematic diagram of the synthesis mechanism of the additive PP-g-CWVR proposed in the present invention. The main component of CWVR is cellulose diacetate, and there are a large number of hydroxyl groups and acetyl groups on the cellulose diacetate molecular chain. First, the anhydride group in PP-g-MAH is ring-opened and undergoes an esterification reaction with a large number of hydroxyl groups on CWVR, thereby reducing the intermolecular forces existing in the CWVR molecule, improving the thermoplastic processing performance, and further helping to improve the thermodynamic properties; at the same time, the additive PP-g-CWVR also exhibits a good compatibilizing effect. The main chain of the additive is PP, and the carboxyl group can also undergo an esterification reaction with the hydroxyl groups on the surface of BF. Therefore, the additive PP-g-CWVR can be used as a compatibilizer in the PP / P-BF blending system.

[0066] Figure 5 Schematic diagram of the BF modification mechanism proposed in the present invention. Figure 5 It can be seen that first, a nucleophilic addition reaction occurs between the acyl chloride groups in PD and the hydroxyl groups on the surface of BF, and the oxygen atom in the hydroxyl group attacks the carbon atom in the acyl chloride to form an ester compound intermediate; then, the intermediate undergoes an elimination reaction, and the chlorine atom leaves the carbonyl chloride to form an ester compound. The surface of BF contains a large number of hydroxyl groups, and PD mainly introduces acyl chloride groups to modify the hydroxyl groups on the surface of BF, thereby improving the compatibility of BF and PP matrix and improving the mechanical properties of bamboo plastic products.

[0067] Figure 6This is a schematic diagram of the mechanism of action of the additive PP-g-CWVR proposed in the present invention in the PP / P-BF system. As can be seen from the figure, there are a large number of carboxyl groups and a small number of unreacted hydroxyl groups on the plasticizing and compatibilizing additive PP-g-CWVR, and there are still hydroxyl groups on the surface of P-BF and unreacted acyl chloride groups on PD. Therefore, during the melt extrusion granulation process in the PP / P-BF system, the additive PP-g-CWVR produces chemical reactions and physical hydrogen bonds, and the molecules are mutually bonded and cross-linked to form a network structure, thereby improving the mechanical strength and heat resistance of the composite material.

[0068] The present invention conducts mechanical property tests on PP samples, comparative example 1 samples and example 1 samples, and the results are shown in Table 3. It can be seen from the table that the modification of BF improves the polarity of BF to a certain extent, which is beneficial to the interlocking with the PP matrix. The reason for the small improvement is that the hydroxyl groups in BF still exist, which is prone to agglomeration, further affecting the interaction of the composite material, resulting in no obvious improvement in mechanical properties. The PP / P-BF composite material with the addition of the plasticizing and compatibility integrated additive PP-g-CWVR has the best mechanical properties, with a maximum tensile strength of 34.22Mpa and a maximum elongation at break of 689%, indicating that the modification reduces the hydroxyl groups in BF, resulting in a decrease in the polarity of the fibers located inside the matrix. In addition, the added additive PP-g-CWVR plays a compatibilizing role, further improving the compatibility between P-BF and PP.

[0069] Table 3 Mechanical properties test of samples

[0070]

[0071]

Claims

1. A method for preparing a polypropylene grafted tobacco waste vinegar residue additive, characterized in that: The method comprises the following steps: carrying out grafting reaction between waste tobacco vinegar residue and polypropylene grafted maleic anhydride in an organic solvent, and obtaining a polypropylene grafted waste tobacco vinegar residue auxiliary agent after precipitation, washing and drying; The mass ratio of polypropylene grafted maleic anhydride to tobacco waste vinegar residue is 1:0.2-0.5; The temperature of the grafting reaction is 115-135°C, and the reaction time is 3-5h.

2. The polypropylene grafted tobacco waste vinegar residue additive prepared by the method as claimed in claim 1.

3. Use of the polypropylene grafted tobacco waste vinegar residue additive as claimed in claim 2 in a PP / modified bamboo powder composite material.

4. The use of the polypropylene grafted tobacco waste vinegar residue additive in the PP / modified bamboo powder composite material according to claim 3, characterized in that: The method comprises the following steps: mixing polypropylene, modified bamboo powder and polypropylene grafted tobacco waste vinegar residue additive at high speed and then performing melt extrusion; The mass ratio of polypropylene, modified bamboo powder and polypropylene grafted tobacco waste vinegar residue additive is 5:1:0.025-0.075; The steps of the method for preparing the modified bamboo powder are as follows: adding the bamboo powder into tetrahydrofuran, then adding triethylamine and phthaloyl chloride to react, and obtaining the modified bamboo powder after precipitation, washing and drying.

5. The use of the polypropylene grafted tobacco waste vinegar residue additive in the PP / modified bamboo powder composite material according to claim 4, characterized in that: The conditions for melt extrusion were: screw speed of 200-300 rpm, feed rate of 5-7 Hz, and extrusion temperature zones of 165, 170, 170, 175, 180, 185, 190, 190, 190, 185, 180°C.

6. The use of the polypropylene grafted tobacco waste vinegar residue additive in the PP / modified bamboo powder composite material according to claim 4, characterized in that: The mass ratio of bamboo powder, triethylamine and phthaloyl chloride is 1:0.05-0.1:0.05-0.1; the reaction temperature is 40-50°C, and the reaction time is 4-6h.

Citation Information

Patent Citations

  • Polypropylene-based wood-plastic composite material and preparation method thereof

    CN103012949A

  • Color master batch based on waste polypropylene and preparation method thereof

    CN114874551A